2020
DOI: 10.1186/s12992-020-00612-0
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the healthy immigrant paradox: decomposing differences in birthweight among immigrants in Spain

Abstract: Background The healthy immigrant paradox refers to the unexpected health advantages of immigrant groups settled in host countries. In this population-based study we analyze immigrant advantages in birthweight decomposing differences between infants born to immigrant mothers from specific origins. Method Using publicly available data from Spanish Vital Statistics for the period 2007–2017, differential birthweights among several groups of immigrants were estimated with an ordinary least squares regression. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…In France, the largest immigrant group, immigrants from the Middle East and North Africa, showed the strongest advantage in birth weight, mirroring similar results previously found in Belgium 18 39. Birth weights of children with Latin-American and Caribbean mothers were significantly lower in the Dutch cohorts, in contrast to findings in previous work in Spain 12 36…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In France, the largest immigrant group, immigrants from the Middle East and North Africa, showed the strongest advantage in birth weight, mirroring similar results previously found in Belgium 18 39. Birth weights of children with Latin-American and Caribbean mothers were significantly lower in the Dutch cohorts, in contrast to findings in previous work in Spain 12 36…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies indicate that geographic origins could be associated with children of immigrants’ birth weight. For example, previous work has highlighted higher birth weights for infants born in Spain to African and Latin-American mothers,12 36 while lower mean birth weights were observed for infants born in China to Asian Indian mothers 37. One of the most interesting findings in our study is that children of South Asian mothers showed consistently lower birth weights, in both BiB-UK (where south Asian immigrants represent the largest immigrant group), ABCD-NL and to a lesser extent in the Raine Study-AU.…”
Section: Discussionsupporting
confidence: 62%
“…Nativity (where an individual is born) also has important implications for preterm birth as it may serve as a proxy for citizenship, acculturation, preferred language, exposure to interpersonal discrimination, or exposure to structural xenophobia . The immigrant paradox is an epidemiologic observation suggesting that non–US-born racial and ethnic groups have better health outcomes, particularly birth outcomes, than their in-country–born counterparts despite experiencing socioeconomic and health care access–related barriers . However, recent literature has found heterogeneity of perinatal outcomes within immigrant communities by race, ethnicity, and country of origin .…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. immigrant population has been increasing rapidly and is expected to be a major driver of population growth ( Guadamuz et al, 2020 , Jordan and Gebeloff, 2022 ). New immigrants are known to have lower incidence of chronic health conditions, a phenomenon described as the healthy immigrant paradox ( Bustamante et al, 2021 , Stanek et al, 2020 ). Nonetheless, disparities in healthcare resources, social disadvantages, neighborhood conditions, and low socioeconomic status associated with excess burden of cardiovascular diseases have also been well-documented among immigrants ( Chang, 2019 , de Mestral and Stringhini, 2017 , Hamad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%